Transtibial Amputation Outcomes Study (TAOS): Comparing Transtibial Amputation With and Without a Tibiofibular Synostosis (Ertl) Procedure. Issue 4 (April 2017) - Bosse, Michael J.; Morshed, Saam; Reider, Lisa; Ertl, William; Toledano, James; Firoozabadi, Reeza; Seymour, Rachel B.; Carroll, Eben; Scharfstein, Daniel O.; Steverson, Barbara; MacKenzie, Ellen J.
Abstract : Summary: The optimal technique for a transtibial amputation in a young, active, and healthy patient is controversial. Proponents of the Ertl procedure (in which the cut ends of the tibia and fibula are joined with a bone bridge synostosis) argue that the residual limb is more stable which confers better prosthetic fit and improved function especially among high-performing individuals. At the same time, the Ertl procedure is associated with longer operative and healing time and may be associated with a higher complication rate compared with the standard Burgess procedure. The TAOS is a prospective, multicenter randomized trial comparing 18-month outcomes after transtibial amputation using the Ertl versus Burgess approach among adults aged 18 to 60. The primary outcomes include surgical treatment for a complication and patient-reported function. Secondary outcomes include physical impairment, pain, and treatment cost. Abstract : Supplemental Digital Content is Available in the Text.